2018
DOI: 10.5588/ijtld.17.0859
|View full text |Cite
|
Sign up to set email alerts
|

Measuring catastrophic costs due to tuberculosis in Viet Nam

Abstract: The proportion of households experiencing catastrophic total costs due to TB in Viet Nam is high, which poses a barrier to TB diagnosis and treatment. Based on study results, programme and partners need to identify key areas for policy action and work towards a national policy guide on intervention to reduce TB patient costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
101
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(127 citation statements)
references
References 1 publication
12
101
3
7
Order By: Relevance
“…Previous surveys done in Africa and Asia have shown that TB patients incur huge catastrophic costs despite free TB treatment. (8,9,11,12) Our study provided additional evidence to this nding. However, catastrophic costs were not homogeneous among the different groups as the poorest households were disproportionally affected and risk of catastrophic costs increased as wealth quintile decreased (5,8,11,12) This makes intuitive sense, and may be attributed to reduced resilience to external shocks such as TB.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous surveys done in Africa and Asia have shown that TB patients incur huge catastrophic costs despite free TB treatment. (8,9,11,12) Our study provided additional evidence to this nding. However, catastrophic costs were not homogeneous among the different groups as the poorest households were disproportionally affected and risk of catastrophic costs increased as wealth quintile decreased (5,8,11,12) This makes intuitive sense, and may be attributed to reduced resilience to external shocks such as TB.…”
Section: Discussionsupporting
confidence: 73%
“…Also, in our context even DS-TB patients experienced higher catastrophic costs than overall costs reported from other low-and middle income countries. (8,9,12,13) High catastrophic costs may negatively impact on both access and adherence to TB treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is witnessed by the low TB burden in countries with high social protection and vice-versa [3]. Evidence from several countries including India shows that TB causes catastrophic economic effects on the patients and their households [4][5][6][7][8][9][10]. Ensuring that no TBaffected families face catastrophic expenditure by 2020 is one of the goals of the END TB strategy of the World Health Organization (WHO) [11].…”
mentioning
confidence: 99%
“…[7][8][9] Another major reason is that adherence to TB treatment protocols represents a heavy economic burden for TB patients in Viet Nam and many other settings due to lost income, travel and opportunity costs. 10,11 A key barrier to effective TB care and prevention is loss to follow-up (LTFU), which is a key contributor to drug resistance, continued transmission and death. 12,13 Nevertheless, 77%-92% of susceptible cases were successfully treated in 2017.…”
Section: Introductionmentioning
confidence: 99%